FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PASIEN TBC SEHINGGA TERCAPAINYA KEBERHASILAN TERAPI - Indriyani, Atika Sri; Sutjiatmo, Afifah B. (Jurnal Buana Farma, 2025)
TB is one of the oldest infectious diseases ever suffered by humans. The infection caused by the Mycrobacterium tuberculosis complex bacteria, known as tuberculosis, usually attacks the lungs, but these bacteria can also infect the bones, brain, or kidneys. One of the obstacles hindering tuberculosis (TB) treatment efforts is adherence. There may have been a decrease in TB cases in recent years due to the increased adherence to TB treatment. Improving tuberculosis (TB) patients' adherence to TB treatment can be achieved through various means, including family communication, healthcare professionals via telemedicine, healthcare professionals with home pharmacy care, and much more. This narrative review method uses primary journal data sources directly collected from the Pubmed and Google Scholar websites. Individuals, families, environments, and medical personnel are factors that influence the success of therapy in TB patients.